An Evaluation of the Performance of the GoBiGas Gasification Process - Karlbrink, Malin (My University, 2015)
The GoBiGas (Gothenburg Biomass Gasification) project was initiated by Göteborg Energi to enable biogas/bio-SNG production through gasification of biomass from forest residuals. The purpose of GoBiGas is to gain knowledge, at a pre-commercial scale, within gasification of forest residues as well as methanation for the purpose of producing biomethane of sufficient quality to be distributed in the conventional gas grid. The performance goal of GoBiGas is that the cold gas efficiency should be at least 65 % and the overall thermal efficiency should be at least 90 %. The aim of this thesis is to establish methods to verify process data and quantify the performance of the gasification process of GoBiGas. Losses in different parts of the process and potential improvements are discussed and proposed. The process data was verified through energy and carbon balances over the gasification process and section. To include variations in the measurements, the process data was randomized with a normal distribution. Using normally distributed data implies that the results from the calculations, such as the efficiencies of the process, were normally distributed with a mean and standard deviation. The method of comparing the normal distributions from the energy and carbon balances did not show any large errors in the measurements of the process data. The cold gas efficiency of the gasification process was within 73 – 80 % and reaching a cold gas efficiency of 65 % over the entire process is possible if less product gas is combusted in the combustion chamber. The overall thermal efficiency of the gasification process was within 80 – 86 %, and to reach an overall thermal efficiency of 90 % over the entire process, the heat losses need to be decreased. The losses in the gasification process could be decreased by; increasing the isolation of the gasification section, decreasing the temperatures in the gasification section, increasing the preheating of steam and air, and combusting less product gas.
Keywords: Energi; Hållbar utveckling; Energiteknik; Energy; Sustainable Development; Energy Engineering